UPAYA PENINGKATAN KUALITAS SUMBER DAYA MANUSIA MELALUI PERAN KKN TEMATIK POSDAYA BERBASIS MASJID DUSUN MANGUNREJO DESA BLAMBANGAN - Riza Faishol; Ahmad Aziz Fanani (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2019)
The mosque is a center of religious activities and community empowerment. The majority of Blambangan Village People are employees in private factories,fishermen, and farmers. Judging by the average environmental Fakor is a hardworking citizen, we are carrying the theme "Synergies towards civil society" with the hope of being able to balance the community environment of Blambangan that Relegius, and productive. Not only productive but also religious by developing science, sharpening, sharpen skills, skill, sensitivity and social care. There are several strategies to achieve all of the potential, including: (1) First strategy, capacity building and human quality, covering various aspects relating to the personal existence of a human being, including: physical conditions, Health, intelligence, mastery of science and skill and spiritual conditions, including faith and steadness to the one true God. With the increasing capacity and quality of people will improve their ability and competitiveness to participate in a variety of social and economic activities and increase the ability of access to various resources in order to meet the needs of Living and improving welfare; (2) Second strategy, improved community welfare in line with the development of Agamis atmosphere and a cool and peaceful family. It is with the support of the community in every religious activities through the routine activities of Jama'ah, Tahlil, Istighostsah and other religious activities so that it is expected to create harmony and peace; (3) The third strategy, increased togetherness and helping each other in all forms.